The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/09291016.2015.1020204
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic regulation of seasonal responses in Indian weaver bird (Ploceus philippinus)

Abstract: Photoperiod (=day length) is the vital factor for the regulation of behavioral and physiological activities in many avian species. This study investigated the seasonal cycles of testicular growth and secondary sexual characteristics of Indian weaver bird under natural day length (NDL) and the effects of duration and intensity of light on photoperiodic induction. In the first experiment, groups of birds (n = 7 each) were exposed to under NDL in April 2008 and May 2009 for 8 and 12 months, respectively. In secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Since, Rowan (1925) first identified that gonadal development in birds breeding at mid to high latitudes was triggered by increasing day length, photoperiodic regulation of avian behavior and breeding has been of continuing interest to researchers. Increasing spring photoperiod has been shown to initiate both pre-nuptial molt and to trigger gonadal development in birds ( Dawson, 1999 , Dawson, 2002 , Dawson et al, 2001 , King, 1968 , Lesher and Kendeigh, 1941 , Pandey and Bhardwaj, 2015 ). As pre-nuptial (also termed pre-alternate) molt is not observed in all species, control mechanisms remain obscure and it is often overlooked in studies of molt in favor of the more common and robust post-nuptial (also termed pre-basic) molt.…”
Section: Introductionmentioning
confidence: 99%
“…Since, Rowan (1925) first identified that gonadal development in birds breeding at mid to high latitudes was triggered by increasing day length, photoperiodic regulation of avian behavior and breeding has been of continuing interest to researchers. Increasing spring photoperiod has been shown to initiate both pre-nuptial molt and to trigger gonadal development in birds ( Dawson, 1999 , Dawson, 2002 , Dawson et al, 2001 , King, 1968 , Lesher and Kendeigh, 1941 , Pandey and Bhardwaj, 2015 ). As pre-nuptial (also termed pre-alternate) molt is not observed in all species, control mechanisms remain obscure and it is often overlooked in studies of molt in favor of the more common and robust post-nuptial (also termed pre-basic) molt.…”
Section: Introductionmentioning
confidence: 99%
“…A pre-nuptial molt occurred between March and June and a post-nuptial molt between October and November (Narasimhacharya et al 1987). The lightning of the bill color starts to cause in August and its turns to a complete straw color in November and depigmented their plumage to the non-breeding type (Rani et al 2007;Pandey & Bhardwaj 2015). The alteration in night light as a bright light during the night alters the resting pattern J TT of this bird it induced a fragmented activity in the early phase of night and enhancement at late night instead of the actual onset of the day (Raap et al 2015;Touitou et al 2017;Kumar et al 2018).…”
Section: Mating Behaviourmentioning
confidence: 99%